Genome-wide association study identified PLCE1- rs2797992 and EGFR- rs6950826 were associated with TP53 expression in the HBV-related hepatocellular carcinoma of Chinese patients in Guangxi - Liao, Xiwen (Am J Transl Res, 2016)
Objective: The genome-wide association approach was employed to explore the association between single nucleotide polymorphisms (SNPs) and TP53 expression in the HBV-related hepatocellular carcinoma (HCC) of Chinese patients in Guangxi. Methods: 403 HBV-related HCC patients were recruited into this study and classified according to the TP53 expression in the cancer by immunohistochemistry. DNA was extracted from the cancer and genotyped with the Human ExomeBeadChip 12v1-1 system; quality control and principal-component analysis (PCA) were applied for data analysis. Results: The Genome-wide association analysis indicated that rs2797992 with a P value of 4.35 × 10(-5) locus in PLCE1 gene and rs6950826 with a P value of 2.2 × 10(-3) locus in EGFR gene were associated with TP53 expression in the HCC. A allele of rs2797992 predicted a decreased risk for TP53 expression in HCC. In contrast, A allele of rs6950826 increased the risk for TP53 expression. There was no strong LD locus in the tested regions. PLCE1 and EGFR were associated with TP53 in pathway and at HCC mRNA level. Conclusion: rs2797992 of PLCE1 gene and rs6950826 of EGFR gene are associated with TP53 expression, but not with the prognosis of HBV-related HCC in HBV-related HCC of Chinese patients in Guangxi.